Implementation of multiple band gaps of quantum wells/dots based on inductively-coupled argon plasma technique - Dong, Nie (2010)
Recently, defect-enhanced interdiffusion, known as intermixing, has been extensively investigated on a wide range of III-V semiconductor quantum well (QW) and quantum dot (QD) structures as a postgrowth process to implement multiple band-gap engergies across a single substrate for monolithic integration of optoelectronic devices. In addition, defect-enhanced interdiffusion provides a unique opportunity to study the interdifussion. In this thesis, defect generation using inductively coupled argon (Ar) plasma (Ar-ICP) exposure, defect-enhanced intermixing and multiple band-gap implementations have been investigated for both InP- and GaAs-based QW and QD structures. In this techinque, the mobile point defects are generated at the near surface region of a structure dut to exposure to ICP Ar plasma and enhance intermixing in the subsequent rapid thermal annealing (RTA) process, whereas band-gap halftones can be achieved in several approaches.